The Influence of Traditional Games (Shaking Cans, Fortifications) on the Level of Physical Fitness of Grade VII Students of SMPN 1 Rambang Niru - Mayang Noventha Melynia; Putri Cicilia Kristina; Siti Ayu Risma Putri (CV. Rayyan Dwi Bharata, 2022)
This study found that the physical fitness of the seventh grade students of SMP Negeri 1 Rambang Niru had a low level. The purpose of this study was to determine the effect of traditional games (Shake Cans, Fort) on the level of physical fitness of seventh grade students of SMP Negeri 1 Rambang Niru. The method used is an experimental method with a one group pretest-posttest research design. The population and sample of the study were 20 students of class VII. Data collection and research instruments using Indonesian physical fitness tests aged 13 to 15 years. Data analysis used the paired sample t test SPSS 16. The results of the study stated that there was an effect of the traditional game of shaking cans and fortifications on the physical fitness of the seventh grade students of SMP Negeri 1 Rambang Niru because Tcount > Ttable (4,819 > 1,729)